Description of a new genus and species of the family Melphidippidae Stebbing, 1899 (Crustacea: Amphipoda) from the deep waters of Brazil - Marques-Junior, Paulo R.; Senna, André R. (Zootaxa, 2013)
The species of the amphipod family Melphidippidae are distributed worldwide in marine habitats, but there is no record of this family from Brazil so far. A new genus and species of Melphidippidae are described from Brazilian waters. Steb-bingiella gen. nov. is monotypic and is distinguished from the other genera of the family by the presence of: antenna 1 with accessory flagellum 7-articulate, lateral cephalic lobe subacute, with globular eyes extremely produced, reaching be-yond the second article of peduncle of antenna 2; gnathopods stout and slightly subchelate; coxae 3 and 4 with strong an-terior projection and coxae 5 and 7 with strong posterior projection; telson cleft, not fully movable, with two globular lobes, about 2X wider than long. Stebbingiella globulosa sp. nov. is the first species of Melphidippidae recorded from Brazilian waters.